PEMBINAAN OLAHRAGA PRESTASI UNGGULAN DI KABAPUTEN MELAWI KALIMATAN BARAT - Rudiansyah, Eko; Soekardi, Soekardi; Hidayah, Taufiq (Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi (Penjaskesrek), 2017)
Abstract: Research objectives 1) analyze the profile of sports in theMelawi Regency area, 2) analyze the condition of human resources at thefeatured sport in Melawi Regency, 3) analyze the condition of thefacilities and infrastructure owned for the featured sports in the MelawiDistrict, 4) analyzing the performance of the branch management incoaching the featured sports branch in Melawi Regency, 5) analyzinggovernment policy in setting expenditure budget funds (APBD) inimproving sports performance in Melawi District.The Data was collectedthrough interview, observation and documentation methods.Researchresult. 1) Sport coaching in Melawi Regency is still under low category;where there are only 5 sports have good performance. 2) The HumanResources of the featured sports branch in Melawi Regency are still ingood category. It is shown that the potency of athletes of the featuredsport has fulfilled the requirements, 3) Sports facilities and infrastructureof the featured sports in Melawi Regency are still in low category, wherethey are not suit the standards, 4) The management performance incoaching the team of superior sports Melawi Regency is still not good. 5)Government policy on sports in Melawi district is still in low category.The funding assistance from the Government is very minimal.Keywords: Coaching, Sports Achievement, Superior SportAbstrak: Tujuan penelitian ini adalah: 1) menganalisis profil olahragayang ada di daerah Kabupaten Melawi, 2) menganalisis kondisi sumberdaya manusia olahraga yang di miliki pada cabang olahraga prestasiunggulan di Kabupaten Melawi, 3) menganalisis kondisi sarana danprasarana yang dimiliki pada cabang olahraga prestasi unggulan diKabupaten Melawi, 4) menganalisis kinerja manajemen pengurus cabangterhadap pembinaan prestasi pada cabang olahraga unggulan diKabupaten Melawi, 5) menganalisis kebijakan pemerintah dalammenetapkan dana anggaran pendapatan belanja (APBD) dalammeningkatkan prestasi olahraga di Kabupaten Melawi. Teknikpengumpulan data yang digunakan adalah wawancara, observasi, dandokumentasi. Hasil penelitian ini adalah: 1) Pembinaan olahraga diKabupaten Melawi masih dikategorikan kurang. Hal ini dikarenakanhanya 5 cabang olahraga yang berprestasi, 2) Sumber daya manusia olahraga pada cabang olahraga unggulan di Kabupaten Melawi masihdikategori baik karena potensi atlet yang dimiliki cabang olahragaunggulan sudah memenuhi syarat, 3) Sarana dan prasarana olahragapada cabang olahraga unggulan di Kabupaten Melawi masihdikategorikan kurang karena tidak sesuai dengan keadaan dan standar, 4)Kinerja manajemen pengurus cabang terhadap pembinaan prestasi padacabang olahraga unggulan di Kabupaten Melawi masih kurang baikkarena kinerja dari cabang olahraga unggulan sebagian masih belum baik.5) Kebijakan pemerintah terhadap olahraga di Kabupaten Melawi masihdalam ketegori kurang karena bantuan dana dari pemerintah sangatminim.Kata Kunci : Pembinaan, Olahraga Prestasi, Unggulan